Development of rGO/Fe3O4 Composites as Glucose Biosensors - Kusumawati, Diah Hari; Mufida, Rahayu Yudia (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2021)
The rGO/Fe3O4 composite is one type of composites that can be used as a biosensor material, especially glucose sensors. The main ingredients of the composite synthesis are graphite and iron sand. The synthesis process of Fe3O4 was done using the coprecipitation method, while the graphite oxidation process was accomplished using the modified Hummer's method. The composites were formed using the ex-situ wet mixing method. The formed iron sand and graphite were characterized using FTIR and XRD, and it was found that Fe3O4 was formed from the appearance of the Fe-O bond, the oxidation process of graphite was seen from the appearance of the C=O bond, and the detection of Fe peaks corresponded to the cubic crystal plane. Likewise, the composites formed were also characterized using FTIR and XRD for identification of the rGO/Fe3O4 composite formation. It was proven from the presence of Fe-O and C-O bonds and the appearance of an amorphous peak of rGO in the XRD results. The performance of theÂ  rGO/Fe3O4 composites as the glucose biosensor was examined by varying the mass of Fe3O4 on the composite, using UV-Vis spectroscopy. The performance of the rGO/Fe3O4 composite biosensor in absorbing glucose reached optimum at a mass variation of 0.3 grams of Fe3O4, as demonstrated by by the lowest absorbance peak with an intensity of 0.0048 at a wavelength of 440 nm, corresponding to glucose entrappment of 7.1 mg/gram.